Świeckość państwa zakwestionowana we Włoszech. Debata na temat krzyży w szkolnych klasach. - Leonetti, Carolina; Filary, Magdalena; Grzelczyk, Mateusz (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
In November 2009 the European Court of Human Rights in Strasbourg ruled that crosses displayed in classrooms of public school are not in agreement with the freedom of religion guaranteed by the European Convention on Human Rights. This ruling was based on the claim that the presence of the Christian symbol limit parents’ right to educate their children in conformity with their own faith and the right of children to believe or not to believe. In Italy, from which the case originates, the Court’s sentence stirred up heated political debates and caused strong public opinion reactions. The verdict was interpreted as a threat to the Catholic-based cultural traditions of the country, despite the traditions not being continued in terms of religious devotion in Italy.